OP0056 Molecular and structural biomarkers of inflammation at 2 years after acute acl injury do not predict structural knee osteoarthritis at 5 years. (12th June 2018) - Roemer, F; Englund, M.; Turkiewicz, A.; Struglics, A.; Guermazi, A.; Lohmander, L.S.; Larsson, S.; Frobell, R.
Abstract : Background: Trauma-induced cytokine response and local inflammation after knee injury may be important in the development of posttraumatic osteoarthritis (OA). It has been reported that synovial fluid levels of inflammatory markers remain increased up to 5 years after anterior cruciate ligament (ACL) injury, indicative of extended local inflammation in the injured joint. 1 Inflammation potentially represents a valid target for treatment in the early and subacute phase after joint trauma in order to prevent or delay onset of post-traumatic knee OA. Objectives: To determine the role of inflammatory biomarkers at 2 years after anterior cruciate ligament (ACL) injury for predicting radiographic and magnetic resonance imaging (MRI)-defined knee OA 5 years post injury. Secondary aim was to estimate the concordance of inflammatory biomarkers assessed by MRI and in synovial fluid. Methods: We studied 113 patients with acute ACL injury. 1.5 Tesla knee MRIs were read for Hoffa- and effusion-synovitis. Biomarkers of inflammation included IL-6, IL-8, IL-10, TNF-α and IFN-γ in serum and synovial fluid, and IL-12p70 in serum. The outcome was radiographic knee OA (ROA) or MRI-defined OA (MROA) at 5 years. Area under receiver operating characteristic curve (AUC), sensitivity and specificity were evaluated in models including MRI features only (M1), inflammation biomarkers only (serum [M2a] – synovial [M2b]) or both MRI and serum [M3a] or synovial [M3b] markers. Linear regression was used for evaluating association between MRI and synovial biomarkers. Results: At 5 years, ROA was present in 26% and MROA was present in 32% of patients' injured knee. The AUCs (95% CI) for ROA were 0.44 (0.42–0.47;M1), 0.62 (0.59–0.65;M2a), 0.58 (0.55–0.61;M2b), 0.53 (0.50–0.56;M3a) and 0.50 (0.46–0.53;M3b) for each model. The corresponding AUCs for MROA were 0.67 (0.64–0.70), 0.49 (0.47–0.52), 0.65 (0.61–0.68), 0.56 (0.52–0.59) and 0.69 (0.66–0.72) (table 1). The associations between MRI and synovial biomarkers were weak and not statistically significant, apart from effusion–synovitis and IL-8 (log 10 IL8 levels were 0.23 and 0.43 higher in persons with grade 1 or 2/3, respectively). Conclusions: Neither MRI-defined inflammation, nor synovial/serum inflammation biomarkers at 2 years as analysed here predicted ROA or MROA at 5 years. The concordance between MRI and synovial inflammatory biomarkers was weak. Additional studies with longer follow-up will be needed to confirm or refute our findings and to more firmly define the role of inflammation for OA development following acute ACL injury. Reference: [1] Struglics A, et al. Changes in cytokines and aggrecan ARGS neoepitope in synovial fluid and serum and in C-terminal crosslinking telopeptide of type II collagen and N-terminal crosslinking telopeptide of type I collagen in urine over five years after anterior cruciate ligament rupture: An exploratory analysis in the knee anterior cruciate ligament, nonsurgical versus surgical treatment trial. Arthritis Rheumatol 2015;67:1816–25. Acknowledgements: We thank the participants of the KANON study without this work would not have been possible. Disclosure of Interest: F. Roemer Shareholder of: Boston Imaging Core Lab (BICL), LLC., M. Englund: None declared, A. Turkiewicz: None declared, A. Struglics: None declared, A. Guermazi Shareholder of: Boston Imaging Core Lab (BICL), LLC., Consultant for: Sanofi-Aventis, Merck Serono, OrthoTrophix, AstraZeneca, Pfizer, GE, and TissuGene, L. S. Lohmander: None declared, S. Larsson: None declared, R. Frobell: None declared